3D Network Binder via In Situ Cross‐Linking on Silicon Anodes with Improved Stability for Lithium‐Ion Batteries. Issue 2 (5th December 2019) - Li, Pengcheng; Chen, Gen; Lin, Yifan; Chen, Fashen; Chen, Long; Zhang, Ning; Cao, Yijun; Ma, Renzhi; Liu, Xiaohe
Abstract: Silicon (Si) has attracted intensive academic and commercial attention due to its extremely high theoretical capacity. However, it is still far away from practical application because of its fast capacity fading, which is caused by the huge volume change. Here, a novel network polymer binder is synthesized through in situ thermal crosslinking of water‐soluble carboxymethyl cellulose (CMC) and maleic anhydride (MAH). The as‐obtained polymer binder network can effectively restrict the huge volume change of Si anodes upon lithiation. Because of the significantly enhanced structural stability, the Si anodes with network polymer binder deliver enhanced electrochemical performance, with a capacity of 996 mAh g −1 at a high current density of 1 A g −1 after 120 cycles under high mass loading. Most importantly, a high average Coulomb efficiency (CE) of 99.4% is obtained, which is superior over the average CE (98.7%) of Si only using CMC as binder. It is considered that this novel 3D network cross‐linking binder can be used for high‐capacity anode materials in next‐generation Li‐ion batteries. Abstract : A novel network polymer binder is synthesized through in situ thermal crosslinking of water‐soluble carboxymethyl cellulose and maleic anhydride. As‐obtained polymer binder network can effectively restrict the huge volume change of Si anodes upon lithiation. Because of the significantly enhanced structural stability, the Si anodes with network polymer binder deliver enhanced electrochemical performance.